Computer simulation of synthesis of yttrium aluminum garnet - Ivanauskas, Feliksas; Kareiva, Aivaras; Lapcun, Bogdanas (Lietuvos matematikos rinkinys, 2003)
A mathematical model of synthesis of yttrium aluminum garnet is presented and used for computer simulation of the synthesis. The model is based on the reaction-diffusion equations. The model takes into concideration structure of the initial reaction’s components. The digital simulation was carried out using the finite difference technique. Relations between rates of reaction and diffusion was investigated.